Finding my dance - Thundercloud, Ria (Penguin Workshop, 2022)
Details member of the Ho-Chunk Nation and Sandia Pueblo Ria Thundercloud's discovery of her love of dance, first through traditional Indigenous styles of jingle dance and the fancy shawl and then through classical styles of tap, jazz, ballet, modern, and contemporary. Explores how Thundercloud felt like an outsider at school as the only Indigenous girl in class, but dance allowed her to express herself and has taken her all around the world as a professional dancer.